ENHANCING COUNTRY IMAGE: A COMPARATIVE STUDY OF TOURISM STRATEGY BETWEEN INDONESIA AND MALAYSIA - Devina Anggiany Putri; Riski Mohamad Baskoro (President University, 2016)
The global competition has become a mandatory phenomenon faced nowadays. Both the emerging economic country and the advanced economic country are competing each other to create and produce something different by maximizing their potentials and performances to obtain more profit that will be impacted to the politic and the economic aspects. Tourism sector is one of the country‟s potentials which has a big role to support the national interests by attaining benefit immensely. Tourism is an efficient industry to earn financial profit and enhance country reputation especially for nations who have abundant of natural resources. As tropical countries, Indonesia and Malaysia government has set up tourism policy which has been outlined into several strategies. The strategies include marketing and promotion activity which purpose to establish public trust towards related countries by inviting more foreign visitors and investors. In responding to this, both countries are branding their nations by doing a public diplomacy in domestic and overseas through tourism activity. This paper will examine the tourism strategy of Indonesia and Malaysia in attempt to increase country image in international community by emphasizing the implementation of public diplomacy in branding the nation through tourism industry during 2010-2015 time frameworks. Thus, we will apply a comparison method in exploring the strengths and weaknesses of tourism strategy in Indonesia and Malaysia.